An evaluation of the concept of living at moderate altitude and training at sea level - Hahn, A. G.; Gore, C. J.; Martin, D. T.; Ashenden, M. J.; Roberts, A. D.; Logan, P. A. (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 2001)
Despite equivocal findings about the benefit of altitude training, current theory dictates that the best approach is to spend several weeks living at >/=2500 m but training near sea level. This paper summarizes six studies in which we used simulated altitude (normobaric hypoxia) to examine: (i) the assumption that moderate hypoxia compromises training intensity (two studies); and (ii) the nature of physiological adaptations to sleeping in moderate hypoxia (four studies). When submaximal exercise was >55% of sea level maximum oxygen uptake (&Vdot;O(2max)), 1800 m simulated altitude significantly increased heart rate, blood lactate and perceived exertion of skiers. In addition, cyclists self-selected lower workloads during high-intensity exercise in hypoxia (2100 m) than in normoxia. Consequently, our findings partially confirm the rationale for 'living high, training low'. In the remaining four studies, serum erythropoietin increased 80% in the early stages of hypoxic exposure, but the reticulocyte response did not significantly exceed that of control subjects. There was no significant increase in haemoglobin mass (Hb(mass)) and &Vdot;O(2max) tended to decrease. Performance in exercise tasks lasting approximately 4 min showed a non-significant trend toward improvement (1.0+/-0.4% vs. 0.1+/-0.4% for a control group; P=0.13 for groupxtime interaction). We conclude that sleeping in moderate hypoxia (2650-3000 m) for up to 23 days may offer practical benefit to elite athletes, but that any effect is not likely due to increased Hb(mass) or &Vdot;O(2max).